2022
DOI: 10.3389/ffgc.2022.1051210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated temperature and abnormal precipitation on soil carbon and nitrogen dynamics in a Pinus densiflora forest

Abstract: Forests have the largest terrestrial nutrient pools. The loss of soil carbon and nitrogen in forests under ongoing climate warming is subject to severe environmental degradation. To mitigate the negative effects of global warming on soil carbon and nitrogen in forest, it is important to obtain a better understanding of how elevated temperature and altered precipitation variability impact soil nutrient dynamics. To explore such interactions, we coupled an eco-hydrological model (Multi-Layer Canopy model, MLCan)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…It has been shown that the warmer ecosystems tend to stimulate the decomposition rates and enzyme activity, which could further decrease soil C and N content. Meanwhile, the higher MAP may greatly enhance soil saturation and water logging, which may further cause nutrient losses through leaching (Chapin et al, 2011; Woo & Seo, 2022). In addition, our study found that MAT and MAP were positively correlated with bacterial Shannon, but negatively correlated with fungal Shannon during forest restoration (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the warmer ecosystems tend to stimulate the decomposition rates and enzyme activity, which could further decrease soil C and N content. Meanwhile, the higher MAP may greatly enhance soil saturation and water logging, which may further cause nutrient losses through leaching (Chapin et al, 2011; Woo & Seo, 2022). In addition, our study found that MAT and MAP were positively correlated with bacterial Shannon, but negatively correlated with fungal Shannon during forest restoration (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Because SOM decomposition has long been understood to be controlled by a combination of several different factors, Mn deposition cannot be interpreted separately from other commonly outlined predictors such as precipitation (moisture), temperature, and N deposition (Berg & Matzner, 1997; Frey et al., 2014; Hartley et al., 2021; Sierra et al., 2015; Woo & Seo, 2022; Zak et al., 2017; L. Zhang et al., 2019; F. Zhao et al., 2021). To include these potential constraints, simple and multilinear regression analyses were carried out with the addition of the three other factors: precipitation, temperature (long‐term mean data from Terrestrial Air Temperature and Precipitation: 1900–2014 Gridded Monthly Time Series data provided by the NOAA PSL, Boulder, Colorado, USA, from their website at https://psl.noaa.gov), and N deposition to test the significance of Mn deposition on topsoil C density.…”
Section: Methodsmentioning
confidence: 99%
“…Because SOM decomposition has long been understood to be controlled by a combination of several different factors, Mn deposition cannot be interpreted separately from other commonly outlined predictors such as precipitation (moisture), temperature, and N deposition (Berg & Matzner, 1997;Frey et al, 2014;Hartley et al, 2021;Sierra et al, 2015;Woo & Seo, 2022;Zak et al, 2017;L. Zhang et al, 2019;F.…”
Section: Correlation Analysis and Interpretation Of Ecological Relevancementioning
confidence: 99%
“…Soil moisture is a critical mediator that regulates the movement and distribution of water and heat energy. It is a widely used variable in multiple disciplines to assess and analyze various phenomena and processes, which include biogeochemical processes (Cain et al., 2022; Wang et al., 2020; Woo & Do, 2021; Woo & Seo, 2022), reservoir management (Devine & O'Geen, 2019; Heinzel et al., 2022), drought and flood (Eswar et al., 2018; del Pilar Jimenez‐Donaire et al., 2020; Lakshmi et al., 2004), irrigation scheduling (Nandan et al., 2021; Woo et al., 2022), and crop yield prediction (Champagne et al., 2019; Woo et al., 2021). Therefore, accurate measurement of soil moisture plays a vital role in Earth system science, ranging from estimating the molecular signatures of microbial decomposition to studying ecosystem responses to global warming (Songara & Patel, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It is a widely used variable in multiple disciplines to assess and analyze various phenomena and processes, which include biogeo-Abbreviations: CNN, convolutional neural network; CRNS, cosmic-ray neutron sensing; DNN, deep neural network; GPR, ground-penetrating radar; MEMS, micro-electromechanical systems; ML, machine learning; RMSE, root mean squared error; TOF, time of flight. chemical processes (Cain et al, 2022;Wang et al, 2020;Woo & Do, 2021;Woo & Seo, 2022), reservoir management (Devine & O'Geen, 2019;Heinzel et al, 2022), drought and flood (Eswar et al, 2018;del Pilar Jimenez-Donaire et al, 2020;Lakshmi et al, 2004), irrigation scheduling (Nandan et al, 2021;, and crop yield prediction (Champagne et al, 2019;. Therefore, accurate measurement of soil moisture plays a vital role in Earth system science, ranging from estimating the molecular signatures of microbial decomposition to studying ecosystem responses to global warming (Songara & Patel, 2022).…”
Section: Introductionmentioning
confidence: 99%